Cyber-victimization and its association with depression among Vietnamese adolescents - Thai, Truc Thanh; Duong, Mai Huynh Thi; Vo, Duy Kim; Dang, Ngan Thien Thi; Huynh, Quynh Ngoc Ho; Tran, Huong Giang Nguyen (PeerJ, 2022)
Background Cyberbullying has become an alarming social issue, but little is known about its prevalence and consequences in many countries. This study investigated the prevalence of cyber-victimization and its association with depression among students in Ho Chi Minh City, Vietnam. Methods A cross-sectional study was conducted in 1,492 students from eight secondary schools and high schools in four urban and suburban areas. Multi-stage cluster sampling approach was used to recruit participants. Students participated in this study on a voluntary basis and completed a self-report questionnaire that included validated scales to measure their experience of cyber-bullying (Cyber Bullying Scale) and symptoms of depression (Center for Epidemiologic Studies–Depression Scale). Weighted logistic regression analysis was used to adjust for the cluster effect and sampling probability. Results Almost all (92.4%) students reported using the internet everyday and nearly 40% used internet for more than four hours per day. Cyber-victimization was identified in 36.5% of students and almost 25% experienced multiple types of cyber-victimization. Nearly half of students reported symptoms of depression. After adjusting for other covariates, students who experienced cyber-victimization were found to have 1.81 times (95% CI [1.42–2.30]) higher in odds of having symptoms of depression. Conclusions Cyber victimization and depression are both common in Vietnamese adolescents. Those who experienced cyber bullying have a higher likelihood of having symptoms of depression. These findings indicate an urgent need for interventions and policies targeting this emerging type of bullying in Vietnam and similar settings due to its potential harmful effects on adolescents’ health.
Keywords: Cyber-victimization; Cyberbullying; Depression; Adolescent; Vietnam